2021
DOI: 10.1177/15579883211049016
|View full text |Cite
|
Sign up to set email alerts
|

Forging Resilience to HIV/AIDS: Personal Strengths of Middle-aged and Older Gay, Bisexual, and Other Men Who Have Sex With Men Living With HIV/AIDS

Abstract: HIV-positive gay, bisexual, two-spirit, and other men who have sex with men (MSM) have exhibited significant resilience to HIV/AIDS in Canada since the start of the epidemic. Since 2012, most of the research that has been conducted on resilience to HIV/AIDS has utilized quantitative methods and deficits-based approaches, with a preferential focus on the plight of young MSM. In order to address apparent gaps in research on HIV/AIDS resilience, we conducted a community-based participatory research qualitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…In the case of TMSM, this reliance on and great appreciation of social engagement, social support, and accessible community resources were distinctly exemplified by the experiences and sentiments described in all three case studies. Several research studies have emphasized the benefits gained by MSM and trans individuals from having perceived social support from LGBTQIA+ friends [ 65 , 66 , 67 , 68 , 69 ], and strong connections with gender-affirming communities and sexual health care [ 46 , 47 , 51 , 52 , 53 , 65 ], especially those that prioritize the elimination of cisgenderism and transphobia [ 70 ]. They have also emphasized the need for such HIV services and programs to create sustainable opportunities to increase the financial security of TMSM, as well as develop more opportunities for TMSM to receive gender affirmation and social support from accessible community resources.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of TMSM, this reliance on and great appreciation of social engagement, social support, and accessible community resources were distinctly exemplified by the experiences and sentiments described in all three case studies. Several research studies have emphasized the benefits gained by MSM and trans individuals from having perceived social support from LGBTQIA+ friends [ 65 , 66 , 67 , 68 , 69 ], and strong connections with gender-affirming communities and sexual health care [ 46 , 47 , 51 , 52 , 53 , 65 ], especially those that prioritize the elimination of cisgenderism and transphobia [ 70 ]. They have also emphasized the need for such HIV services and programs to create sustainable opportunities to increase the financial security of TMSM, as well as develop more opportunities for TMSM to receive gender affirmation and social support from accessible community resources.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific study of resilience among HIV/AIDS populations has continued to grow in the 21st century [11,14,15]. Researchers focused on strengths-based approaches for developing interventions to address various issues related to HIV/AIDS have increasingly recognized the important role of resilience in the focus of their scholarly work [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different groups affected by HIV/AIDS, ethnoracially diverse, middleaged and older men who have sex with men (MSM) living with HIV/AIDS have been the specific subpopulation that has been impacted by HIV/AIDS the longest [18,19], and likely the group that has exhibited resilience to HIV/AIDS the most since the beginning of the epidemic [20]. Evidence of resilience to HIV/AIDS among middle-aged and older MSM has been documented and discussed in research articles [21][22][23], and consequently, resilience to HIV/AIDS has been reported to be key to the successful aging of MSM living with HIV/AIDS [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations